Changes in Colour attributes of Kithul (Caryota urens) flour stored in Refrigerated (4°c) Condition - Wijesinghe, J.A.A.C.; Wicramasinghe, I.; Saranandha, K.H. (European Journal of Academic Essays, 2015)
Attached

Colour o f the food is the first consideration for quality evaluated by consumers. This paper is aimed to evaluate the colour as to define criteria for differentiation of fresh and one year old flour samples. Kithul flour (Caryota urens) colour were evaluated in terms o f lightness (L.*) value , redness(a*) value .yellowness (b*) values as well as the total colour difference(AE). Kithul flour samples which were collected from five main growing areas presented significant difference (p< 0.05) among their colour attributes during shelf life which was stored in refrigerated condition (4°C). According to the instrumental measurements, lightness value has significantly changed (P<0.05) by improving after one year time period. Nevertheless redness and yellowness value has not significantly changed after one year time period. However redness has improved while yellowness has decreased with the time .According to the colour attributes o f flour samples Matale (AE=34.77) and Kegalle (AE=34.65) had a greater deviation from the standard colour value than the other samples. Kandy area presented the least deviation from standard as AE=30.24 at the initial stage. With the time colour difference has decreased for all samples. In the case o f Kurunegala (AE=29.50) and Kandy (AE=29.37) flour are shown least colour deviation than other three areas. However time could be directly influence on reduction o f colour difference (AE) o f flour although it was stored in refrigerated and air-tightened condition. However this can be a focal point for food applications in future to choose better storage condition to keep original colour o f the flour.
Keywords: Kithul flour; Refrigerated condition; Colour variation; storage condition; shelf life; L* a* b* values